Lutetium 177 PSMA radionuclide therapy for men with prostate cancer: a review of the current literature and discussion of practical aspects of therapy. Issue 1 (March 2017) - Emmett, Louise; Willowson, Kathy; Violet, John; Shin, Jane; Blanksby, Ashley; Lee, Jonathan
Abstract : This article provides a practical overview of Lu 177 PSMA therapy for prostate cancer. It discusses the practical aspects of administration, radation safety and dosing. It also gives an overview of currently published trials in clinical efficacy. Abstract: Prostate‐specific membrane antigen (PSMA) is a receptor on the surface of prostate cancer cells that is revolutionising the way we image and treat men with prostate cancer. New small molecule peptides with high‐binding affinity for the PSMA receptor have allowed high quality, highly specific PET imaging, in addition to the development of targeted radionuclide therapy for men with prostate cancer. This targeted therapy for prostate cancer has, to date, predominately used Lutetium 177 (Lu) labelled PSMA peptides. Early clinical studies evaluating the safety and efficacy of Lu PSMA therapy have demonstrated promising results with a significant proportion of men with metastatic prostate cancer, who have already failed other therapies, responding clinically to Lu PSMA. This review discusses the practical issues of administering Lu PSMA, and gives an overview of the findings from currently published trials in regards to treatment response rates, expected toxicities and safety.